Exercise training for health-related quality of life in peripheral artery disease: A systematic review and meta-analysis. (February 2015) - Parmenter, Belinda J; Dieberg, Gudrun; Phipps, Glenn; Smart, Neil A
We sought to quantify whether health-related quality of life (HRQoL) is improved through exercise training in people with peripheral artery disease (PAD) and to clarify which prescriptions were optimal for improving HRQoL when compared to usual care. We conducted a systematic search (PubMed, CINAHL, Cochrane Central Register of Controlled Trials; 1966 – 31 August 2014). We only included randomized controlled trials (RCTs) of exercise training versus usual medical care in persons with PAD that included the Walking Impairment Questionnaire (WIQ) and Short-Form Health Survey component summary scores as outcomes. Of 15 RCTs, 1257 participants were studied: 543 participated in supervised exercise, with only 61 undertaking resistance training and 316 unsupervised exercise. When compared to controls, participants who completed any form of exercise training significantly improved their WIQ speed [mean difference (MD) 9.60 (95% CI 6.98 to 12.23, p <0.00001)]; WIQ distance [MD 7.41 (95% CI 4.49 to 10.33, p <0.00001)] and WIQ stair-climbing [MD 5.07 (95% CI 3.16 to 6.99, p <0.00001)]. Walking also significantly improved the Short-Form Physical Component Summary (SF-PCS) score when compared to controls [MD 1.24 (95% CI 0.48 to 2.01, p =0.001)], but not the Mental Component Summary (SF-MCS) score [MD –0.55 (95% CI –1.27 to 0.18, p =0.14)]. Exercise training improves the SF-PCS dimension, as well as perceived walking distance, speed and stair-climbing as measured by the WIQ, but not the SF-MCS score. Future studies should aim to blind assessors of such subjective measures, and study alternative modes and prescriptions of exercise alternative to walking.